Weekend effect in non‐elective abdominal aortic aneurysm repair - Ambler, G. K. (BJS Open, 2017)
BACKGROUND: The ‘weekend effect’ describes the phenomenon where patient outcomes appear worse for those admitted at the weekend. It has been used recently to justify significant changes in UK health policy. Recent evidence has suggested that the effect may be due to a combination of inadequate correction for confounding factors and inaccurate coding. The effects of these factors were investigated in patients with acute abdominal aortic aneurysm (AAA). METHODS: Patients undergoing non‐elective AAA repair entered into the UK National Vascular Registry from January 2013 until December 2015 were included in a case–control study. The patients were divided according to whether they were treated during the week (Monday 08.00 hours to Friday 17.00 hours) or at the weekend. Data extracted included demographics, co‐morbidities, preoperative medications and baseline blood test results, as well as outcomes. Coding issues were investigated by looking at patients treated for ruptured, symptomatic or asymptomatic AAA within the non‐elective cohort. The primary outcome was in‐hospital mortality. Secondary outcomes included length of inpatient stay, and cardiac, respiratory and renal complications. RESULTS: The mortality rate appeared to be higher at the weekend (odds ratio (OR) 1·69, 95 per cent c.i. 1·47 to 1·94; P < 0·001), but this effect disappeared when confounding factors and coding issues were corrected for (corrected OR for ruptured AAA 1·09, 0·92 to 1·29; P = 0·330). Differences in outcomes were similar for prolonged length of hospital stay (uncorrected OR 1·21, 95 per cent c.i. 1·06 to 1·37, P = 0·005; corrected OR for ruptured AAA 1·06, 0·91 to 1·10, P = 0·478), and morbidity outcomes. CONCLUSION: After appropriate correction for confounding factors and coding effects, there was no evidence of a significant weekend effect in the treatment of non‐elective AAA in the UK.